Higher risk of wheeze in female than male smokers. Results from the Swedish GA 2 LEN study. - Anders Bjerg (Public Library of Science (PLoS), 2013)
Background Women who smoke have higher risk of lung function impairment, COPD and lung cancer than smoking men. An influence of sex hormones has been demonstrated, but the mechanisms are unclear and the associations often subject to confounding. This was a study of wheeze in relation to smoking and sex with adjustment for important confounders. Methods In 2008 the Global Allergy and Asthma European Network (GA(2)LEN) questionnaire was mailed to 45.000 Swedes (age 16-75 years), and 26.851 (60%) participated. "Any wheeze": any wheeze during the last 12 months. "Asthmatic wheeze": wheeze with breathlessness apart from colds. Results Any wheeze and asthmatic wheeze was reported by 17.3% and 7.1% of women, vs. 15.8% and 6.1% of men (both p<0.001). Although smoking prevalence was similar in both sexes, men had greater cumulative exposure, 16.2 pack-years vs. 12.8 in women (p<0.001). Most other exposures and characteristics associated with wheeze were significantly overrepresented in men. Adjusted for these potential confounders and pack-years, current smoking was a stronger risk factor for any wheeze in women aged <53 years, adjusted odds ratio (aOR) 1.85 (1.56-2.19) vs. 1.60 (1.30-1.96) in men. Cumulative smoke exposure and current smoking each interacted significantly with female sex, aOR 1.02 per pack-year (p<0.01) and aOR 1.28 (p = 0.04) respectively. Female compared to male current smokers also had greater risk of asthmatic wheeze, aOR 1.53 vs. 1.03, interaction aOR 1.52 (p = 0.02). These interactions were not seen in age ≥ 53 years. Discussion In addition to the increased risk of COPD and lung cancer female, compared to male, smokers are at greater risk of significant wheezing symptoms in younger age. This became clearer after adjustment for important confounders including cumulative smoke exposure. Estrogen has previously been shown to increase the bioactivation of several compounds in tobacco smoke, which may enhance smoke-induced airway inflammation in fertile women.